PENGEMBANGAN KREATIVITAS DALAM BUKU PELAJARAN KERAJINAN TANGAN DAN KESENIAN UNTUK SISWA KELAS 5 SD - Ika Lestari (Perspektif Ilmu Pendidikan, 2007)
The objective of this research is to describe the aspects of creativity in Keratin Tongan Dan Keening (Handcraft and Arts), a main textbook, used in the fifth grade of Elementary School. The aspects of creativity are identified as personality, motivator, process and product. This research employed2 content analysis method based on the data gathered by studying the whole book. It is found out that this book does not contain all aspects of creativity as expected in a textbook for Handcraft and Arts. This research, therefore, suggests some recommendation for writing a textbook for Handcraft and Arts.